KORELASI ANTARA PARITAS DENGAN KEJADIAN PERDARAHAN POSTPARTUM PRIMER - Sibuea, Rony (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to determine the correlation between parity and the incidence of primary postpartum hemorrhage. The research design used is a cross-sectional correlation design. This study was conducted at the Public Health Center (Puskesmas) in Pulau Untung Jawa Village, Kepulauan Seribu Selatan District, DKI Jakarta in 2021. The population in this study was mothers who experienced postpartum hemorrhage (500 ml/more) at gestational age ≥ 20 weeks in the first 24 hours after delivery. The sampling technique used in this study was saturated sampling. The data were analyzed using the Chi-squared test. From the results of the study, it was found that 29 cases of primary postpartum hemorrhage occurred. Most incidences of primary postpartum hemorrhage occurred at a high parity level (more than 1) as many as 20 cases (68.97%). After analyzing the data using the Chi-squared test based on dk = 1 and α = 0.05, the Chi-square table = 3.48 while the calculated Chi-square count = 4.16. The conclusion is obtained by comparing X² count with X² table, it is found that X² count is > X² table, which means that there is a correlation between parity and the incidence of primary postpartum hemorrhage. It means that women with high parity have a greater risk of experiencing primary postpartum hemorrhage. With the high incidence of primary postpartum hemorrhage at high parity, it is hoped that healthcare facilities can provide more intensive services. Preventive measures should be started since women are pregnant by doing good antenatal care, providing information about the occurrence of primary postpartum hemorrhage and paying attention to predisposing factors or history of primary postpartum hemorrhage.